Il filosofo e il suo doppio. Husserl tra fenomenologia, sofistica e contro-storia della filosofia - Majolino, Claudio (Bollettino Filosofico, 2024)
This essay addresses the relationship between phenomenology, the history of philosophy, and sophistry. Its aim is to emphasize the originality of Husserl’s claim according to which the sophist is, somehow, the “doppelganger” of the philosopher. At first, two main figures in the phenomenological tradition are examined: Brentano and Heidegger. Both authors, in fact, also discussed the role of sophistry in the history of philosophy. The way in which Husserl conceives the history of the idea of philosophy and the historical function of Protagoras and, especially, Gorgias are then examined in detail. After a series of comparative remarks, this essay concludes by highlighting the philosophical function of the confrontation between philosophy and sophistry as it is emphasized by Husserl. Keywords: Brentano, Heidegger, History of Philosophy, Husserl, Sophists